Impact of social support on the resilience of youth: mediating effects of coping styles - Cao, Fei; Li, Juan; Xin, Wei; Cai, Nan (Frontiers in Public Health, 2024)
Chinese youth are at high risk for depression with a significantly higher detection rate of depression risk than other age groups, which brings about a huge challenge to the mental health work of universities. Developing supportive resources that promote resilience against adverse environmental influences in high-risk groups is quite more urgent than medical treatment for firm diagnoses of mental issues that have developed into depression in the current background. Based on stress theory, this study explores mechanisms that facilitate the development of resilience in young people with regard to social support and coping styles. We conducted a survey on 665 university students, the results of which indicate that: (1) social support has a significant positive effect on psychological resilience of the youth; (2) mixed coping and immature coping styles have significant negative impact on both social support and resilience, while mature coping styles having a significant positive effect on social support and resilience; (3) mature and immature coping styles mediate the association between social support and resilience in youth. The current research depicts an interventional perspective of building a social support network that guides the youth to adopt mature coping styles to enhance their resilience and facilitate their mental health.